2012
DOI: 10.1590/s1415-43662012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Ocupação e adequação do uso das terras na microbacia do Ribeirão Extrema, Distrito Federal: Parte I

Abstract: A sustentabilidade ambiental dos agroecossistemas do Distrito Federal (DF) vem sendo ameaçada em função do grande desenvolvimento das atividades agrícolas. O objetivo do presente estudo foi a avaliação do uso e ocupação das terras da microbacia do Ribeirão Extrema/DF, com o auxílio de técnicas de Sensoriamento Remoto e Geoprocessamento. Utilizou-se uma imagem de satélite LANDSAT ETM+, ano 2010, classificada usando-se o software ENVI 4.1, por meio do qual foi gerado o mapa de uso e ocupação das terras da microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
1
3
0
5
Order By: Relevance
“…Kobayashi et al (2019) considered such confusion as expected due to spectral resemblance between these targets (Figure 4). Similar results were related by Lago et al (2012) when they assessed land-use adequacy in this region in 2011. Novais et al (2016) classified land-use using MAXVER on Landsat imagery, and they obtained satisfactory results for a watershed in the Northwest of Brazil.…”
Section: Classification Of Land-use In Ribeirão Extrema Microwatershedsupporting
confidence: 81%
See 2 more Smart Citations
“…Kobayashi et al (2019) considered such confusion as expected due to spectral resemblance between these targets (Figure 4). Similar results were related by Lago et al (2012) when they assessed land-use adequacy in this region in 2011. Novais et al (2016) classified land-use using MAXVER on Landsat imagery, and they obtained satisfactory results for a watershed in the Northwest of Brazil.…”
Section: Classification Of Land-use In Ribeirão Extrema Microwatershedsupporting
confidence: 81%
“…Several authors have used this methodology, including Lago et al (2012), who showed satisfactory results in assessing land-use and occupation adequacy in the regions studied. Souza et al (2015) also studied land-use adequacy in a watershed in São Paulo State, Brazil, and had identified pastures and fields occupying places with overuse could be playing the role of primary vegetation in these areas.…”
Section: Adequacy Of Land-use and Occupation Of The Study Area In 2019mentioning
confidence: 99%
See 1 more Smart Citation
“…Só assim é possível construir conhecimento das capacidades e limitações de uma região. Ressalta-se, no entanto, a necessidade de uma atualização constante desses registros, para que as tendências sejam detectadas (Lago et al, 2012). A melhor maneira de monitorar essas mudanças é através da utilização de produtos multi-temporais de sensoriamento remoto (Gao et al, 2001;Lopes et al, 2010), que fornecem dados importantes sobre as características ambientais.…”
Section: Revista Brasileira De Engenharia Agrícola E Ambientalunclassified
“…Estudos científicos recentes têm demonstrado que trabalhos preventivos são ferramentas eficientes para proteção dos recursos naturais e, portanto, das águas subterrâneas (HIRATA, 1994;ERTEL et al, 2012). Diante deste desafio, incentivar o mapeamento e identificação das diferentes fragilidades do meio frente à contaminação dos recursos hídricos mostra-se uma importante fonte de subsídio técnico-científico na gestão e conservação destes recursos (LAGO et al, 2012;FI-JANI et al, 2013;MENEZES et al, 2013;COELHO et al, 2013).…”
Section: Introductionunclassified